THE CONSEQUENCES OF HUMANITARIAN PEACEKEEPING IN AFRICA - Ferreira, Rialize (Scientia Militaria - South African Journal of Military Studies, 2011)
Owing to the changing nature of international conflict, the 1990s witnessed agrowing need for humanitarian peacekeeping operations, especially in Africa. Thereluctance of the United Nations to be involved in peacekeeping operations in Africacompelled South Africa to take part in peacekeeping to assist neighbouring conflictriddenstates. There is, however, a discrepancy between the conceptualisation andapplication of peacekeeping and peace-enforcement operations. This notion ismanifest in the changing nature of post-Cold War conflicts and requisite strategies,doctrines and operational procedures to execute these operations. A shift in SouthAfrican defence policy was necessary to accommodate an expanded mandate tomake provision for African peacekeeping missions. These humanitarian missionsunfortunately also have unintended, latent consequences for the host populations,which can harm the peace operations as such.The aim of this article is to investigate traditional peacekeeping shifting topeace-building as a manifest, intended consequence and the way in whichunintended, latent consequences of peacekeeping come about.